Association between phase angle and all-cause mortality in adults aged 18–49 years: NHANES 1999–2004 - Xia, Xian-xin; Li, Chuan-xiang; Xue, Xin-xin; Chen, Ya-jun; He, Fang; Guo, Hong-rong (Scientific reports, 2025)
Phase angle (PhA) is an indicator of nutritional status. The association between PhA and all-cause mortality has been confirmed in older adults, but no relevant studies have been conducted in adults aged 18–49 years. This study aimed to investigate the relationship between PhA and all-cause mortality in adults aged 18–49 years. Our study included 6338 adults aged 18–49 from the National Health and Nutrition Examination Survey (1999–2004). Kaplan-Meier (KM) curve, multiple Cox regression and stratified analyses were performed. These adults were divided into two groups based on the median PhA value (the low PhA group: PhA < 6.96°; the high PhA group: PhA ≥ 6.96°). During a median follow-up of 214 months, 307 all-cause deaths were recorded. The all-cause mortality rate was 5.07% in the low PhA group and 3.98% in the high PhA group. After full adjustment, a higher PhA value was significantly associated with reduced risk of all-cause mortality (HR = 0.73,95CI%:0.59–0.91, P = 0.005). Similarly, compared with those in the low PhA group, individuals in the high PhA group had a lower risk of all-cause mortality (HR = 0.67, 95% CI 0.46–0.98, P = 0.041). There was an interaction between smoking status and PhA ( P for interaction = 0.029), with a statistically significant negative association between PhA and all-cause mortality in the non-smokers (HR:0.62, 95%CI:0.53–0.88, P = 0.003). In conclusion, there was a significant negative association between PhA and all-cause mortality in adults aged 18–49 years. The negative association was stronger in non-smokers.